Efektivitas Pembelajaran Pendidikan Kewarganegaraan Melalui Metode Discovery Learning Pada Sekolah SMK Kertanegara Kuaro - Arma Okgi Nugroho; Zulfitria Zulfitria (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim to be achieved in this research is to find out the effectiveness of civic education learning through the Discovery Learning method for vocational school students. The method used is qualitative where the data collection mechanism used is through field observations and interviews with informants, namely teachers and students. The results of this research show that the Discovery Learning learning mechanism is able to create student independence in studying citizenship education. Students better understand learning concepts by having discussions with peers. Apart from that, the success obtained from this successful learning is that students' grades increase.